Os saberes necessários à prática da gestão escolar: uma análise da formação dos gestores escolares - Cordeiro, Márcio Roque (2024)
The present work results from the proposal for Analysis of the Practice of School Managers, especially those who perform the role of School Director, based on the study of their training and their performance in state schools located in the municipality of Maracanaú–CE. We begin the work by presenting a historical account of School Management, with regard to the Election for School Director in public schools in the State Network since the 90s, until the present day, including highlighting the differentiated Process, according to specific legislation with regard to to State Schools of Professional Education. Thus, this qualitative work had the general objective of evaluating the Practice of School Managers, in a special way, the Teachers who perform the role of Director of state schools located in the municipality of Maracanaú–CE. To this end, the perspective of In-Depth Assessment by Rodrigues (2016) was followed, with emphasis on 3 of its axes, namely: trajectory/temporality, content and territorial spectrum/temporality. In this sense, bibliographic, documentary and field research was used. The field research was conducted in the municipality of Maracanaú, located in the metropolitan region of Fortaleza/Ceará, through semi-structured interviews, reaching the participation of 25 subjects linked to the school councils of the 3 state schools researched, one being a regular high school. , a Full-Time High School and a State School of Professional Education. Thus, this qualitative work had the general objective of evaluating the Practice of School Managers, in a special way, the Teachers who perform the role of Director of state schools located in the municipality of Maracanaú–CE. To this end, the perspective of In-Depth Assessment by Rodrigues (2016) was followed, with emphasis on 3 of its axes, namely: trajectory/temporality, content and territorial spectrum/temporality. In this sense, bibliographic, documentary and field research was used. The field research was conducted in the municipality of Maracanaú, located in the metropolitan region of Fortaleza/Ceará, through semi-structured interviews, reaching the participation of 25 subjects linked to the school councils of the 3 state schools researched, one being a regular high school. , a Full-Time High School and a State School of Professional Education. The results reveal significant advances in school autonomy with regard to administrative and financial execution, especially with regard to the School Council and the Executing Unit, however, it is noticeable that although Managers are elected or appointed after an entire selection process, the Management is not exercised through a democratic and participatory stance, and the School Council, in some cases, does not exercise its duties as guided by its legislation and regulations. Thus, there remain challenges to be faced and areas to be improved, requiring a continuous process of evaluation and improvement of the work of School Management and the School Council. Finally, we suggest a Product, as a proposal for CREDE 1/SEDUC regarding the continued training of Teachers who perform the role of School Director.